THE CONTRIBUTION OF ENGLISH PROFICIENCY, LEARNING MOTIVATION, AND SOCIAL SUPPORT TO ACCOUNTING STUDENTS’ PROFESSIONALISM AND LEARNING STRATEGIES IN THE GLOBAL ERA - Rochamzan, Suhartina; Zulkifli (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to analyze the contribution of English proficiency, learning motivation, and social support to accounting students’ professionalism and learning strategies in the global era. The rapid globalization requires students to possess not only technical skills but also effective international communication abilities. In this context, English proficiency is crucial for accounting students to access international literature and understand global standards. Additionally, high learning motivation encourages students to be more disciplined and active in academic activities, while social support from the academic environment plays a role in enhancing their confidence and professionalism. This research uses a quantitative approach with a survey involving 200 accounting students from various universities in Makassar, South Sulawesi. The analysis results show that all three factors significantly impact students’ professionalism and learning strategies. English proficiency is positively correlated with improved professionalism and learning strategies, while learning motivation enhances students' professionalism quality, and social support plays an essential role in developing professional attitudes and improving learning strategies. The findings emphasize the importance of integrating these three factors into higher education curricula to prepare students for global challenges and enhance their competitiveness in the international job market.